Housing market volatility connectedness among G7 countries. Issue 3 (6th February 2018) - Lee, Hahn Shik; Lee, Woo Suk
ABSTRACT: This study investigates international linkages among housing markets in the G7 countries, using the connectedness methodology developed in Diebold and Yilmaz (2012, 2015). We find that volatility connectedness varies over the business cycle, with a surge during the global financial crisis. We also show that the United States and Italy were major net transmitters of housing market volatility shocks to other countries during the global financial crisis and the European debt crisis, respectively.